Perbedaan Efektivitas Durasi Penerapan Kangaroo Mother Care (KMC) Terhadap Peningkatan Berat Badan Bayi (BBLR ) - Komang Yogi Triana; Ni Luh Putu Mey Ani; Desak Putu Risna Dewi (Sekolah Tinggi Ilmu Kesehatan Kesdam IX/Udayana, 2022)
Background: Babies with low birth weight have a high risk of death and disability during their growth period. Nurses need to take a role in reducing the risks that may occur in babies with low birth weight. The baby's weight gain is one of the absolute requirements to pursue the appropriate growth stage. Kangaroo Mother Care method is one of the most commonly used intervention options today. However, the difference in the duration of Kangaroo Mother Care implementation is still a matter of debate for many parties. This study aims to analyze the difference in the effectiveness of Kangaroo Mother Care duration of 1 hour and 2 hours on increasing the weight of babies with low birth weight. Methods: This research is a quasi-experimental research using a pre-posttest design approach with control group design. Respondents in this study were babies with birth weight 1500-2500 grams in the Neonatal Intensive Care Unit in September-November 2020, totaling 30 respondents. Sample selection was done by purposive sampling. Results: This study showed a significant difference in weight gain in low birth weight infants after performing Kangaroo Mother Care with a duration of two hours compared to a duration of one hour. Conclusion: The Kangaroo Mother Care program with a duration of two hours is recommended to be applied to premature babies or low birth weight babies to optimize baby growth and development care.